Chronostratigraphic Subdivision of the Cambrian of China - Sanchi Peng (Geologica Acta, 2003)
The chronostratigraphic framework for the Cambrian of South China is reviewed. Currently four series and nine stages are recognized. The Cambrian of South China is subdivided into one pre-trilobite-bearing series, the Diandongian Series, and three trilobite-dominated series, the Qiandongian, Wulingian, and Hunanian. The nine stages are, in ascending order, the Jinningian, Meishucunian, Nangaoan, Duyunian, Taijiangian, Wangcunian, Youshuian, Waergangian, and Hunanian. All of these units have been named recently and are boundary-strato-type- based, with the lower boundaries being defined by the first appearances of characteristic species, most of which hold potential for long-range correlation.